2014
DOI: 10.1186/s12870-014-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mechanisms underlying yield potential in the rice high-yielding cultivar Takanari, based on reciprocal chromosome segment substitution lines

Abstract: BackgroundIncreasing rice yield potential is a major objective in rice breeding programs, given the need for meeting the demands of population growth, especially in Asia. Genetic analysis using genomic information and high-yielding cultivars can facilitate understanding of the genetic mechanisms underlying rice yield potential. Chromosome segment substitution lines (CSSLs) are a powerful tool for the detection and precise mapping of quantitative trait loci (QTLs) that have both large and small effects. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 33 publications
3
101
0
Order By: Relevance
“…CSSL- GN1 was developed by repeated backcrossing with Koshihikari and marker-assisted selection 16 . NIL- APO1 was developed in the same way.…”
Section: Methodsmentioning
confidence: 99%
“…CSSL- GN1 was developed by repeated backcrossing with Koshihikari and marker-assisted selection 16 . NIL- APO1 was developed in the same way.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in a similar way of our previous successful trial [30], we screened frame SSR markers for linkage map construction from data of about 2000 SSRs [31] which are initial representative of the 18,000 [23]. Then, we selected 196 polymorphic SSR markers and one InDel marker (Gn1) [32] distributed evenly in the rice genome. Total genomic DNA was extracted from fresh leaves by the cetyltrimethylammonium bromide (CTAB) method [33] and amplification conditions for the selected SSR markers were as in [34].…”
Section: Dna Marker Analysis and Qtl Analysismentioning
confidence: 99%
“…An indica ‐type high‐yielding cultivar, ‘Takanari’, was developed in 1990 (Imbe et al., ). Takanari originates from high‐yielding indica cultivars including ‘IR8’; it has the sd1 gene and is shorter in plant stature than normal temperate japonica cultivars in Japan (Takai et al., ). Recent yield trials reported that Takanari produced the highest brown rice yield (11.7 t ha −1 ) on record in Japan (Nagata, Sasaki, Ohdaira, & Yoshinaga, ; Takai et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Takanari originates from high‐yielding indica cultivars including ‘IR8’; it has the sd1 gene and is shorter in plant stature than normal temperate japonica cultivars in Japan (Takai et al., ). Recent yield trials reported that Takanari produced the highest brown rice yield (11.7 t ha −1 ) on record in Japan (Nagata, Sasaki, Ohdaira, & Yoshinaga, ; Takai et al., ). The high yield was achieved because of large panicles, a high leaf photosynthetic ability, the high accumulation of non‐structural carbohydrates in the culm and leaf sheath at the full heading stage, and the translocation of many of these carbohydrates into panicles during grain filling (Kanemura, Homma, Ohsumi, Shiraiwa, & Horie, ; Ohsumi et al., ; Takai et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation